Greenwitch - Cooper, Susan, 1935- (New York : Margaret K. McElderry Books, 1997)
Jane's invitation to witness the making of the Greenwitch begins a series of sinister events in which she and her two brothers help the Old Ones recover the grail stolen by the Dark.
Booklist.
Child Study Children's Book Committee.
Library Journal.
5.3
6.9
5-8.
Keywords: Fantasy; Cornwall (England : County) -- Fiction; England -- Fiction; Fantastic fiction